2018
DOI: 10.12659/msm.909655
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Expression Profiling of Bone Marrow Mesenchymal Stem Cells in Steroid-Induced Osteonecrosis of the Femoral Head Associated with Osteogenesis

Abstract: BackgroundSteroid-induced osteonecrosis of the femoral head (SONFH) is a common orthopedic disease associated with the application of glucocorticoid (GC). In this study, we detected the microRNAs (miRNAs) differentially expressed in bone marrow mesenchymal stem cells (BMSCs) from SONFH patients, and target gene predictions were performed, and the functions of the target genes was verified.Material/MethodsBMSCs collected from patients with SONFH and femoral neck fracture (FNF) constituted the SONFH group (n=3) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
0
23
0
Order By: Relevance
“…Twenty-two differentially expressed miRNAs were identified in bone marrow mesenchymal stem cells (BMSCs) from patients with steroid-induced femoral head necrosis, 17 were upregulated and five were downregulated. During osteogenic differentiation of BMSCs, hsa-mir-601, hsa-mir-452-3p, hsa-mir-647, hsa-mir-516b-5p, and hsa-mir-127-5p were significantly downregulated, while hsa-mir-122-3p was significantly upregulated, suggesting that different miRNAs promoted or inhibited osteogenic differentiation [19]. miRNAs and their identified target genes in the osteogenic differentiation of BMSCs are summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-two differentially expressed miRNAs were identified in bone marrow mesenchymal stem cells (BMSCs) from patients with steroid-induced femoral head necrosis, 17 were upregulated and five were downregulated. During osteogenic differentiation of BMSCs, hsa-mir-601, hsa-mir-452-3p, hsa-mir-647, hsa-mir-516b-5p, and hsa-mir-127-5p were significantly downregulated, while hsa-mir-122-3p was significantly upregulated, suggesting that different miRNAs promoted or inhibited osteogenic differentiation [19]. miRNAs and their identified target genes in the osteogenic differentiation of BMSCs are summarized in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the expression level of hsa-miR-122-3p in the group at Ficat stage IV was found to be lower than that in the stage III group, suggesting that the expression level of hsa-miR-122-3p in BMSCs may be correlated with the progression of steroid-induced ONFH. Wang et al [13] profiled the miRNA expression in three patients with steroid-induced ONFH and three patients with femoral neck fracture and identified 17 upregulated and five downregulated miRNAs in the steroid-induced ONFH group. Moreover, in an in vitro study, they identified five miRNAs (miR-601, miR-452-3p, miR-647, miR-516b-5p, and miR-127-5p) with decreased levels and one miRNA (miRNA-122-3p) with an increased level during osteogenic differentiation, whereas the changes in the expression levels during adipogenic differentiation were in the opposite direction.…”
Section: Mirna Expression Profiles In Bone Marrow Mesenchymalmentioning
confidence: 99%
“…As we all know, this nail is theoretically contra-indicated for cervical femoral fractures due to the rotational forces applied on the femoral head during the insertion of the lag screw. These forces lead to severe and inacceptable rotation of the fracture site and usually displace the fracture in a pejorative manner [24][25][26][27].…”
Section: Which Treatment Which Surgery?mentioning
confidence: 99%